Resource allocation in multihop cellular networks - Li, Xue Jun (2008)
Multihop cellular networks (MCNs) incorporate the flexibility of ad hoc networks into traditional single-hop cellular networks (SCNs). In this thesis, we study the resource allocation problem in MCNs. We first present a comprehensive survey on the existing proposals for MCN architectures. Next, we propose two different channel assignment schemes—asymmetric fixed channel assignment (AFCA) and multihop dynamic channel assignment (MDCA) for MCNs. The performance of AFCA is analyzed using two multi-dimensional Markov Chain models, which are validated through computer simulations. Results show that AFCA significantly increases the system capacity as compared to the convention FCA in SCNs. For MDCA, it assigns channels based on the interference information with two developed channel searching strategies. Results show that MDCA with SCS or PCS outperforms AFCA for MCNs. The final part of this thesis is on the medium access control (MAC) schemes. We first investigate the performance of PRMA in TDD-CDMA SCNs with power control. Next, we propose a PRMA-based MAC scheme，namely multihop MAC (MMAC), for TDD-CDMA MCNs with fixed relay stations (RSs). Simulation results show that MCNs with the proposed MMAC scheme outperform SCNs when the cell radius is large.